Kinetic effect of the taping on the ankle during a change of direction in basketball players - Valencia, O.; Saka, C.; Ramos, C.; Caparrós-Manosalva, C.; Guzmán-Venegas, R. (Journal of Human Sport & Exercise, 2021)
The purpose of this study was to compare the kinetic effect, with (WT) and without (WoT) the use of ankle taping, during a change of direction in basketball players. Twenty-two players were evaluated (11 men, 11 women; age = 21.50 ± 1.74 years, mass = 72.80 ± 13.14 kg, height = 1.71 ± 0.11 m). The functional task of "change of direction in 60°" was registered with a 3D motion analysis system and a force plate. The torques of eversion, plantarflexion, and ankle joint reaction force were evaluated during the braking phase, using an inverse dynamics method. To compare between conditions a t-student or Wilcoxon tests were used. The results revealed that the use of ankle taping yield a decrease in the anterior joint reaction force (WoT = 4.21 ± 1.36 N/kg vs WT = 2.92 ± 1.07 N/kg, p < .0001) and the eversion torque (WoT = 0.56 ± 0.24 Nm/kg vs WT = 0.51 ± 0.20 Nm/kg, p = .02) during a change of direction in 60º. In conclusion, according to the sample of assessed basketball players, the use of this bandage could contribute to the functional stability of the ankle, decreasing the torque of fibularis muscles and the shear anterior-posterior between the shank-foot segments.